The effects of riparian restoration following saltcedar (Tamarix spp.) biocontrol on habitat and herpetofauna along a desert stream. Issue 1 (18th September 2015) - Mosher, Kent R.; Bateman, Heather L.
Abstract : Amphibians and reptiles (herpetofauna) have been linked to specific microhabitat characteristics, microclimates, and water resources in riparian forests. Our objective was to relate variation in herpetofauna abundance to changes in habitat caused by a beetle used for Tamarix biocontrol ( Diorhabda carinulata ; Coleoptera: Chrysomelidae) and riparian restoration. During 2013 and 2014, we measured vegetation and monitored herpetofauna via trapping and visual encounter surveys (VES) at locations affected by biocontrol along the Virgin River in the Mojave Desert of the southwestern United States. Twenty‐one sites were divided into four riparian stand types based on density and percent cover of dominant trees ( Tamarix, Prosopis, Populus, and Salix ) and presence or absence of restoration. Restoration activities consisted of mechanically removing non‐native trees, transplanting native trees, and restoring hydrologic flows. Restored sites had three times more total lizard and eight times more yellow‐backed spiny lizard ( Sceloporus uniformis ) captures than other stand types. Woodhouse's toad ( Anaxyrus woodhousii ) captures were greatest in unrestored and restored Tam‐Pop/Sal sites. Results from VES indicated that herpetofauna abundance was greatest in the restored Tam‐Pop/Sal site compared with the adjacent unrestored Tam‐Pop/Sal site. Tam sites were characterized by having high Tamarix cover, percent canopy cover, and shade. Restored Tam‐Pop/Sal sites were most similar in habitat to Tam‐Pop/Sal sites. Two species of herpetofauna (spiny lizard and toad) were found to prefer habitat components characteristic of restored Tam‐Pop/Sal sites. Restored sites likely supported higher abundances of these species because restoration activities reduced canopy cover, increased native tree density, and restored surface water.